2014
DOI: 10.1128/jvi.01327-14
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Genotypic Diversity and Establishment of 2009 H1N1 Pandemic-Origin Internal Genes in Pigs in China

Abstract: IMPORTANCEShortly after the emergence of the 2009 pandemic H1N1 (pdm/09) influenza virus, it was transmitted from humans to pigs and this continues to occur around the world. Many reassortants between pdm/09-origin viruses and enzootic swine influenza viruses (SIVs) have been detected. However, the long-term impact of pdm/09-origin viruses on the SIV gene pool, which could lead to the generation of influenza viruses with the potential to infect humans, has not been systematically examined. From extensive surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
96
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 44 publications
(66 reference statements)
7
96
1
Order By: Relevance
“…A possible explanation is that the TRIG lineage is more permissive to reassortment with H1N1pdm09 and incorporation of internal genes. Reassortants with H1N1pdm09-TRIG internal genes were also more frequently detected in China, and the reassortants that circulated the longest had at least five H1N1pdm09-origin genes (16). These Chinese H1N1pdm09 reassortants became predominant with time, and the authors speculated that the H1N1pdm09 internal genes replace the Eurasian and TRIG internal genes in China (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the TRIG lineage is more permissive to reassortment with H1N1pdm09 and incorporation of internal genes. Reassortants with H1N1pdm09-TRIG internal genes were also more frequently detected in China, and the reassortants that circulated the longest had at least five H1N1pdm09-origin genes (16). These Chinese H1N1pdm09 reassortants became predominant with time, and the authors speculated that the H1N1pdm09 internal genes replace the Eurasian and TRIG internal genes in China (16).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the introduction of H1N1pdm09 into pigs was concurrent with an increase in genetic diversity at the whole-genome and surface gene levels of contemporary swine IAV. Reassortment events between endemic swine and H1N1pdm09 viruses have been reported in many countries (8,10,14,15), and viruses containing different constellations of H1N1pdm09 internal genes are now predominant among IAV circulating in Chinese pigs (16). In the United States, the M gene from H1N1pdm09 quickly replaced the TRIG M gene, but other H1N1pdm09 internal genes were also detected (5,17).…”
mentioning
confidence: 99%
“…Since pigs may facilitate the introduction of avian viruses or viral genes to humans, transmission of avian H9N2 viruses to pigs raises concerns over the possible generation of human pandemic influenza strains (9). This has been heightened since the emergence of the swine-origin 2009 H1N1 pandemic influenza virus (28,29) and the subsequent rapid expansion of the genetic diversity of swine influenza viruses (30,31).…”
mentioning
confidence: 99%
“…In the United States, the TRIG lineage was the predominant lineage prior to 2009. Recent records have shown that the H1N1pdm09 viruses have reassorted extensively with other co-circulating swine IAV in both H1 and H3 subtypes [9,22,23,26] and gradually replaced the dominant TRIG lineage internal genes, especially the pdm-lineage M gene [23,24,27]. All eight pdm-lineage genes were detected in our study in various combinations with TRIG-lineage genes.…”
Section: Discussionmentioning
confidence: 59%
“…The introduction of human seasonal IAV to swine and reassortment has been associated with subsequent antigenic evolution in multiple swine IAV lineages, including in southern China [24] and Europe [25]. Multiple internal Table 1.…”
Section: Discussionmentioning
confidence: 99%